2010
DOI: 10.1177/1028315310375306
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Nursing Students Who Study Abroad: A Qualitative Inquiry

Abstract: Nurse Researchers need to explore study abroad programs and identify their impact on the development of cultural competence and global perspectives in nursing students. The purpose of this study was to explore the lived experience of nursing students who study abroad and to identify benefits and impediments that may be used to spawn future research and shape existing and future study abroad programs. The research question for this phenomenological study was "What is the lived experience of nursing students who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 30 publications
4
58
0
1
Order By: Relevance
“…• Cultural competency study are supported by similar themes reported in the literature (Edmonds, 2010;Mkandawire-Valhmu & Doering, 2012) study abroad programs differ in length and destinations making comparisons difficult across studies. However, programs reported in the literature were similar in goals and objectives to this program.…”
Section: Categories Themesmentioning
confidence: 86%
See 2 more Smart Citations
“…• Cultural competency study are supported by similar themes reported in the literature (Edmonds, 2010;Mkandawire-Valhmu & Doering, 2012) study abroad programs differ in length and destinations making comparisons difficult across studies. However, programs reported in the literature were similar in goals and objectives to this program.…”
Section: Categories Themesmentioning
confidence: 86%
“…A phenomenological study (Edmonds, 2010) was conducted with 18 American nursing students who travelled to Dominica or England participated in a one-week study abroad program. "Four themes were evident as a result of the study: recognizing, encountering, adapting and mastering" (Edmonds, 2012, p. 33).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the health professions, increasing numbers of medical, nursing, and pharmacy students are participating in international learning or service experiences. [2][3][4] Students who study outside of the United States at some point during their academic careers tend to develop a greater appreciation for cultural differences, learn to discard stereotypes, and increase their level of cultural awareness. 3 Health professions students who have participated in international clinical experiences have demonstrated benefits such as heightened clarity about career roles, including those related to underserved multicultural populations, increased compassion toward patients, increased appreciation for and confidence in clinical skills, and increased awareness of resource use.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Students who study outside of the United States at some point during their academic careers tend to develop a greater appreciation for cultural differences, learn to discard stereotypes, and increase their level of cultural awareness. 3 Health professions students who have participated in international clinical experiences have demonstrated benefits such as heightened clarity about career roles, including those related to underserved multicultural populations, increased compassion toward patients, increased appreciation for and confidence in clinical skills, and increased awareness of resource use. 5,6 Pharmacy students and academicians recognize the importance of a global perspective with regard to health and disease, and their interest in seeking experiential opportunities around the world is growing.…”
Section: Introductionmentioning
confidence: 99%